A Review on Cost Effective Physical Activity Using Bike (International Journal of Food and Nutritional Sciences, 2022)
A cost-benefit study of utilizing bike/pedestrian paths in Lincoln, Nebraska, to decrease health care expenses related with inactivity was performed from a public health viewpoint. The information was gathered from the city's Recreational Trails Census Report from 1998 and the literature. The trails cost $209.28 per person per year ($59.28 for construction and upkeep, $150 for equipment and travel). The yearly direct medical benefit per capita from utilizing the trails was $564.41. The cost-benefit ratio was 2.94, meaning that every dollar spent on paths for physical exercise resulted in $2.94 in direct medical benefit. According to the sensitivity studies, the ratios varied from 1.65 to 13.40. As a result, constructing trails is cost-effective from the standpoint of public health. Equipment and travel expenses were the most sensitive factors influencing the cost-benefit ratios; nevertheless, even at the greatest cost, every $1 invested in trails led in a higher return in direct medical benefit.